Komposisi Hasil Tangkapan Sodo’ (Scoop Net) di Kecamatan Mallusetasi Kabupaten Barru - Hasmawati, H; Aras, Muhammad; Usman, U; Sulaiman, Muhammad; Ilyas, I (Journal Galung Tropika, 2022)
District, Barru Regency, use a scoop (scoop net), or in local terms, it is known as Sodo’, making it their main fishing tool using light aids. The purpose of this study was to determine the composition of the catch of sodo’ (scoop net) operated in Mallusetasi District, Barru Regency. Data collection was carried out in May – September 2021. The method used in this study was a survey method with observation, interviews, and documentation. Data collection was carried out with seven repetitions (7 trips) of operation, namely 7 times at night and 7 times in the early morning. The data collected was then analyzed descriptively. The results showed that the composition of the catch obtained at night was dominated by one to two types of fish caught: anchovies and reborn shrimp. While the fishing operations in the early hours varied in terms of type and size, consisting of anchovies, tembang fish, mackerel, tuna, flying fish, and pepetek.